Multinucleated Giant Cells in Ameloblastoma: An Uncommon Finding - Bhattarai, Sunny; Shrestha, Ashish; Keshwar, Shashi (Birat Journal of Health Sciences, 2022)
Ameloblastoma is a benign, slow growing and locally aggressive odontogenic tumor. Typical histopathological findings include islands, strands, sheets, cords of variable size with core of loosely arranged cells in reticular pattern and peripheral layer of palisading cuboidal to columnar cells. An uncommon event in this is presence of multinucleated giant cells. These cells are formed by the fusion of cells usually of monocyte or macrophage lineage and presence of these cells is indicative of the disease process. This case series affirms the presence of multinucleated giant cells in the different histopathological patterns of ameloblastoma. These cells may be related to the aggressive nature of the pathology. However, the origin and nature of the giant cells in the present case series could not be established. Further evaluation of more cases and investigations needs to be done to identify the nature and origin of these cells.